A DFT study of the unusual substrate-assisted mechanism of Serratia marcescens chitinase B reveals the role of solvent and mutational effect on catalysis - Jitonnom,J. (Elsevier Inc., 2015)
© 2014 Elsevier Inc. All rights reserved. Serratia marcescens chitinase B (SmChiB) catalyzes the hydrolysis of β-1,4-glycosidic bond, via an unusual substrate-assisted mechanism, in which the substrate itself acts as an intramolecular nucleophile. In this paper, the catalytic mechanism of SmChiB has been investigated by using density functional theory. The details of two consecutive steps (glycosylation and deglycosylation), the structures and energetics along the whole catalytic reaction, and the roles of solvent molecules as well as some conserved SmChiB residues (Asp142, Tyr214, Asp215, and Arg294) during catalysis are highlighted. Our calculations show that the formation of the oxazolinium cation intermediate in the glycosylation step was found to be a rate-determining step (with a barrier of 23 kcal/mol), in line with our previous computational studies (Jitonnom et al., 2011, 2014). The solvent water molecules have a significant effect on a catalytic efficiency in the degycosylation step: the catalytic water is essentially placed in a perfect position for nucleophic attack by hydrogen bond network, lowering the barrier height of this step from 11.3 kcal/mol to 2.9 kcal/mol when more water molecules were introduced. Upon the in silico mutations of the four conserved residues, their mutational effects on the relative stability of the reaction intermediates and the computed energetics can be obtained by comparing with the wild-type results. Mutations of Tyr214 to Phe or Ala have shown a profound effect on the relative stability of the oxazolinium intermediate, emphasizing a direct role of this residue in destabilizing the intermediate. In line with the experiment that the D142A mutation leads to almost complete loss of SmChiB activity, this mutation greatly decreases the stability of the intermediate, resulting in a very large increase in the activation barrier up to 50 kcal/mol. The salt-bridges residues (Asp215 and Arg294) were also found to play a role in stabilizing the oxazolinium intermediate.